The Influence of Emotional Intelligence on Academic Procrastination Through Learning Burnout: A Meta-Analytic Study - Dwi Nur Luthofah; Widodo; Merry Lapasau (Jurnal Penelitian Pendidikan IPA, 2026)
This study investigates the mediating role of academic burnout in the relationship between emotional intelligence and academic procrastination, a pathway not previously examined through meta-analytic synthesis. Following predetermined inclusion and exclusion criteria, 24 empirical studies published between 2015 and 2025 were retrieved from SpringerLink, ScienceDirect, Scopus, and ResearchGate, yielding a combined sample of 6,901 participants. All analyses were conducted under a random effects model. Heterogeneity was substantial across pathways, with I² reaching approximately 86% in the burnout-to-procrastination path, justifying the chosen model. Funnel plot inspection revealed no strong evidence of publication bias for the two main pathways, though the emotional intelligence-to-procrastination path showed minor asymmetry attributable to a single outlier study. The pooled effect sizes showed that emotional intelligence negatively predicted academic burnout (r = –0.34, p < 0.001), and academic burnout strongly predicted academic procrastination (r = 0.73, p < 0.001), while the direct effect of emotional intelligence on procrastination was non-significant (r = –0.15, p = 0.255). A product-of-coefficients meta-analytic mediation analysis confirmed that the indirect effect through burnout was significant, with the non-significant direct effect indicating full mediation. These findings are consistent with Conservation of Resources Theory and the strength model of self-control. Interventions targeting burnout prevention alongside emotional intelligence development are recommended as evidence-based strategies for reducing academic procrastination among university students.